ANALISIS KEBUTUHAN BAHAN BACAAN ANTI BULLYING UNTUK OPTIMALISASI GERAKAN ANTIBULLYING DI SD NEGERI 1 SUMITA - Pradnyana, Putu; Pradana Putra, Gede Adhi (Dharmas Education Journal (DE_Journal), 2024)
Based on the discussion review, it can be concluded that the results of this study are that there are differences in perception between teachers and Principals regarding the frequency of bullying incidents. The majority of teachers stated that bullying rarely occurs, while Principals identified that bullying often occurs. This difference indicates the need for relevant reading materials to improve understanding of bullying, both for students and teachers. Teachers agree that anti-bullying reading materials are very important in helping students understand the negative impacts of bullying and instilling anti-violence values. This study suggests the development of anti-bullying reading materials that are interesting, easy to understand, and supported by images in order to increase students' awareness and interest in understanding the issue of bullying. In addition to the research findings, best practices in this study include the following: Development of Interesting and Relevant Reading Materials, Involvement of Teachers in the Anti-Bullying Literacy Process, Use of Reading Materials as Discussion Tools, Combination with Guidance and Counseling Programs, Collaboration Between Schools and Parents, and Developing special guidelines containing practical steps in handling bullying cases at school.